2009
DOI: 10.1002/ijc.24195
|View full text |Cite
|
Sign up to set email alerts
|

Shikonin exerts antitumor activity via proteasome inhibition and cell death induction in vitro and in vivo

Abstract: Dysregulation of the ubiquitin-proteasome pathway plays an essential role in tumor growth and development. Shikonin, a natural naphthoquinone isolated from the traditional Chinese medicine Zi Cao (gromwell), has been reported to possess tumor cellkilling activity, and results from a clinical study using a shikonincontaining mixture demonstrated its safety and efficacy for the treatment of late-stage lung cancer. In this study, we reported that shikonin is an inhibitor of tumor proteasome activity in vitro and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
118
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 152 publications
(124 citation statements)
references
References 34 publications
5
118
0
1
Order By: Relevance
“…Cell death was quantified using an AnnexinV-FITC/PI kit and FACSCalibur flow cytometry as described previously (17). Cells were plated at a density of 2×10 5 cells per well in sixwell plates and incubated overnight, and were then treated with either vehicle or Sanggenon C as indicated.…”
Section: Cell Death Assaymentioning
confidence: 99%
“…Cell death was quantified using an AnnexinV-FITC/PI kit and FACSCalibur flow cytometry as described previously (17). Cells were plated at a density of 2×10 5 cells per well in sixwell plates and incubated overnight, and were then treated with either vehicle or Sanggenon C as indicated.…”
Section: Cell Death Assaymentioning
confidence: 99%
“…In the last four decades, shikonin, alkannin and their derivatives have been investigated as potential anticancer drugs for various aspects of cancer treatment (Ahn et al, 1995;Papageorgiou VP et al, 1999;Bailly, 2000;Kim et al, 2001;Masuda et al, 2003Masuda et al, , 2004Nakaya and Miyasaka, 2003;Han et al, 2007;Hu and Xuan, 2008;Xuan and Hu, 2009;Yang et al, 2009), including a clinical study (Guo et al, 1991), which indicated that a shikonin mixture was effective in treating 19 patients of later-stage lung cancer who were not suitable for operation, radiotherapy and chemotherapy. We previously reported that shikonin and its analogs induced cell death with characteristics of necroptosis, a basic cell death defined by Degterev et al and further studied in depth by the same group of scientists (Degterev et al, 2005Hitomi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Shikonin and its analogues can kill cancer cells through a number of mechanisms, including inhibition of topoisomerase-I (11), polo-like kinase 1 (PLK1) and protein tyrosine kinase (PTK) (12); regulation of phosphorylation-dependent activities of extracellular-regulated protein kinase (pERK), c-Jun N-terminal kinase (JNK) and protein kinase Ca (PKCa) (13); suppression of tumor necrosis factor receptor-associated protein 1 (TRAP1) expression (14); activation of caspases (15) and inhibition of proteasome activity (16). In previous studies, shikonin and its derivatives were shown to exert antiproliferative and pro-apoptotic effects against a number of tumor cells, including sarcoma 180 (S-180) ascites cells, gastric cancer, colon adenocarcinoma and oral cancer (17).…”
Section: Introductionmentioning
confidence: 99%